2021
DOI: 10.1007/s10212-021-00543-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of motivating teaching behaviour and student engagement: a microanalytic approach

Abstract: Positive student engagement is a prerequisite for students’ educational success. In this study, a microanalytic approach was used to explore patterns in teachers’ use of specific motivating teaching behaviours from the perspective of self-determination theory in relation to indicators of students’ positive engagement. The lessons of 52 teachers were observed and event-based coded. Results showed that specifically asking motivating questions and providing positive feedback and support during exercises were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 77 publications
3
17
1
Order By: Relevance
“…According to this study, in an online learning environment, autonomy-supportive teaching motivations positively affected students' intrinsic motivation and student engagement. This has also been confirmed in previous studies (Cents-Boonstra et al, 2021;Matos et al, 2018). In contrast, controlling teaching motivations also had positive impacts on extrinsic motivation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to this study, in an online learning environment, autonomy-supportive teaching motivations positively affected students' intrinsic motivation and student engagement. This has also been confirmed in previous studies (Cents-Boonstra et al, 2021;Matos et al, 2018). In contrast, controlling teaching motivations also had positive impacts on extrinsic motivation.…”
Section: Discussionsupporting
confidence: 87%
“…This finding was also supported by Assor et al (2002) who showed that controlling teaching motivations could not be consistently effective on student engagement. Furthermore, the utility of controlling teaching motivations needs to be considered with its relevance to a given context (Cents-Boonstra et al, 2021). In addition, there was no association between student extrinsic motivation and student engagement in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Demotivation results from external factors (Wang and Littlewood, 2021 ). Before this, existing of motivation is a prerequisite because its gradual decrease is later named demotivation (Cents-Boonstra et al, 2022 ). In other words, the absence of motivation can be named demotivation or motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though synchronous online teaching can help students and teachers interact with each other (Caton et al ., 2021), engaging students in virtual classrooms is a major concern for teachers. Compared to traditional settings, students have lesser ways to be engaged with the institution in virtual learning environment (Cents-Boonstra et al ., 2022). The new generation of students often gets distracted by social media and other digital communication tools during the virtual classes (Dhawan, 2020).…”
Section: Introductionmentioning
confidence: 99%